Lake House, Cressy, Tasmania, ca. 1970, 1 - Stacey, Wes (Wesley), 1941-2023. (1968)
Depicting neo classical villa, pilaster, porch, windows, roofline.
Part of the Wes Stacey archive of architectural photographs, 1968-1972.
Catalogue record generated as part of a batch load.
Title from acquisitions document, see file NLA09/703.
Wes Stacey reference number: 2 18 5.
Also available online
Keywords: Two-story houses -- Tasmania -- Cressy -- Photographs; Neoclassicism (Architecture) -- Tasmania -- Cressy -- Photographs; Architecture, Colonial -- Tasmania -- Cressy -- Photographs; Cressy (Tas.) -- Buildings, structures, etc. -- Photographs